Biomass Components and Environmental Controls in Ningxia Grasslands - Kai-bo WANG; Jian-ping LI; Zhou-ping SHANGGUAN (Journal of Integrative Agriculture, 2012)
Grassland plays an important role in the global carbon cycle and climate regulation. However, there are still large uncertainties in grassland carbon pool and also its role in global carbon cycle due to the lack of measured grassland biomass at regional scale or global scale with a unified survey method, particular for below-ground biomass. The present study, based on a total of 44 grassland sampling plots with 220 quadrats across Ningxia, investigated the characteristics of above-ground biomass (AGB), below-ground biomass (BGB), litter biomass (LB), total biomass (TB) and root: shoot ratios (R:S) for six predominantly grassland types, and their relationships with climatic factors. AGB, BGB, LB and TB varied markedly across different grassland types, the median value ranging from 28.2-692.6 g m−2 for AGB, 130.4-2 036.6 g m−2 for BGB, 9.2-82.3 g m−2 for LB, and 168.0-2 681.3 g m−2 for TB. R:S showed less variation with median values from 3.2 to 5.3 (excluding marshy meadow). The different grassland types showed similar patterns of biomass allocation, with more than 70% BGB for all types. There is evidence of strong positive effects associated with mean annual precipitation (MAP) and negative effects associated with mean annual temperature (MAT) on AGB, BGB, and LB, although both factors have the opposite effect on R:S.